A critical review of the Cochrane meta‐analysis of routine late‐pregnancy ultrasound. (28th July 2020) - Smith, GCS
Abstract : A Cochrane review of universal late‐pregnancy ultrasound has been highly influential in guiding UK practice, concluding that it does not improve outcome. However, the meta‐analysis combines trials that used diverse definitions of screen positive, were designed in the absence of high‐quality data on diagnostic effectiveness and did not couple screening to an effective intervention. Moreover, even if the trials had combined a highly effective screening test with a highly effective intervention, the sample size was 15% of that required to study perinatal death. It is not known whether universal late‐pregnancy ultrasound confers benefit on the mother or baby. Tweetable abstract: Despite >50 years of research, we do not know whether universal late‐pregnancy ultrasound confers benefit on the mother or baby. Tweetable abstract: Despite >50 years of research, we do not know whether universal late‐pregnancy ultrasound confers benefit on the mother or baby.